2020
DOI: 10.3390/cells9020332
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Controls Sulphur Metabolism in the Rosette Leaves of Arabidopsis and Facilitates S Remobilization to the Seeds

Abstract: Sulphur deficiency in crops became an agricultural concern several decades ago, due to the decrease of S deposition and the atmospheric sulphur dioxide emissions released by industrial plants. Autophagy, which is a conserved mechanism for nutrient recycling in eukaryotes, is involved in nitrogen, iron, zinc and manganese remobilizations from the rosette to the seeds in Arabidopsis thaliana. Here, we have compared the role of autophagy in sulphur and nitrogen management at the whole plant level, performing conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Autophagy is also involved in recycling of micronutrients, such as zinc and sulfur in plant cells (Eguchi et al, 2017; Lornac et al, 2020; Tarnowski et al, 2020). In Arabidopsis , zinc limitation induces the accumulation of autophagosomes (Eguchi et al, 2017).…”
Section: Physiological Roles Of Plant Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is also involved in recycling of micronutrients, such as zinc and sulfur in plant cells (Eguchi et al, 2017; Lornac et al, 2020; Tarnowski et al, 2020). In Arabidopsis , zinc limitation induces the accumulation of autophagosomes (Eguchi et al, 2017).…”
Section: Physiological Roles Of Plant Autophagymentioning
confidence: 99%
“…More recently, two independent studies uncovered an indispensable role of autophagy in sulfur metabolism. (Lornac et al, 2020) observed that in the Arabidopsis atg5 mutants, the remobilization of sulfur from rosettes to seeds is compromised. Furthermore, the selective autophagy receptor NBR1 is likely important for plant responses to sulfur deficiency (Tarnowski et al, 2020), suggesting that selective autophagy may improve the efficiency of micronutrient remobilization from the vacuole.…”
Section: Physiological Roles Of Plant Autophagymentioning
confidence: 99%
“…Although there are no other data on sulfur metabolism and its homeostasis in autophagy mutants, we could assume similar mechanisms. Further studies revealed the role of autophagy in sulfur management at the whole plant level by the application of 34 S isotope labeling on atg5 mutant and wild type plants [126]. Sulfur remobilization from the rosette to seed was impaired in atg5 mutant and most of the amino acids, including methionine and cysteine, accumulated in the rosette leaves of atg5 mutant, irrespective of sulfur supply.…”
Section: Selective Degradation Via Autophagy In the Regulation Of Sulmentioning
confidence: 99%
“…Recently, Chen et al [ 28 ] have shown that the overexpression of AtATG8s ( AtATG8a , AtATG8e , AtATG8f and AtATG8g ) with different promoters enhanced autophagosome number, promoted autophagy activity and increased the N remobilization efficiency under optimal N conditions without a negative effect on yield or biomass. Besides N, autophagy is also involved in recycling other nutrients, such as iron, zinc, manganese and sulfur [ 29 , 30 , 31 ]. Despite the characterization of the involvement of ATG8s in N remobilization and the participation of autophagy in recycling other nutrients in a number of plant species, little is known about them in tea plant.…”
Section: Introductionmentioning
confidence: 99%